Implementasi Pendidikan Karakter Islam Melalui Pembelajaran Pendidikan Agama Islam Di Era Digital Di Perguruan Tinggi Umum - Kartini K (CV. SINAR HOWUHOWU, 2026)
Following the digital revolution, many aspects of human life have changed, including education. The integration of Islamic character education through Islamic Religious Education (PAI) in higher education institutions, particularly state universities, is becoming increasingly important to address moral and ethical challenges among students. This study aims to analyze the implementation of Islamic character education through PAI learning in the digital era. The method used is a qualitative method combined with literature research. The results show that Islamic character education can be successfully implemented through the use of innovative learning strategies, the application of digital media, and the reinforcement of values such as honesty, responsibility, discipline, and tolerance. However, problems such as digital distractions and the lack of integration of character lessons are still important. Therefore, to optimize character education in the digital era, teachers, institutions, and students must work together.